FABRIKASI DAN KARAKTERISASI MATERIAL Ba DENGAN MENGGUNAKAN DIFRAKSI SINAR-X0.9 Sr 0.1 TiO 3 - ', Nurmairanti; Dewi, Rahmi; Ginting, Mbantun (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This study is to determine the crystal structure of Ba0.9Sr0.1TiO3 with X-ray diffraction. The process of making the material Ba0.9Sr0.1TiO3 is mixing the powder material Barium Carbonate (BaCO3), Strontium Carbonate (SrCO3) and Titanium Dioxide (TiO2) which uses solid state reaction method with a ratio 0.9: 0.1: 1. Furthermore, the compounds are mixed and crushed using a mortal after it is heated at 4000C for 15 minutes and made the pellets by using Hydraulic Press. Pellets that have been made is heated for 1 hour with 600, 700 and 8000C and characterized using X-ray diffraction. The result is in the form of 2Ө angle as a function of intensity. The highest peak of the threesamples contained the hkl plane (1 1 0) at for 2Ө = 31.760 is 1045 (au) for temperature of 8000C,while the lowest peak contained the hkl plane (2 1 0) is the diffraction angle 2Ө = 51.240 with 113intensity (au) at a temperature of 6000C.